2011
DOI: 10.1007/s10295-010-0903-6
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic approach to enhance doxorubicin production in panK-integrated Streptomyces peucetius ATCC 27952

Abstract: Biosynthesis of polyketide compounds depends upon the starter and extender units of coenzyme A derivatives of carboxylic acids present in the host organism. To increase the coenzyme A (CoA) pool, pantothenate kinase (panK) gene from Escherichia coli was integrated into S. peucetius ATCC 27952 (panK-integrated strain, BG200), which resulted in increase in aglycone polyketide ε-rhodomycinone (RHO), but decrease in the desired product, i.e., doxorubicin (DXR). To reduce RHO accumulation by synthesizing daunorubic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…For example, weak export of the antitumor polyketide doxorubicin from S. peucetius cells has been recently shown to decrease the overall productivity of the strain (Malla et al 2010, Song et al 2011). A similar situation probably applies to many recombinant pathways (Ostash et al 2010a), effectively limiting the potential of combinatorial biosynthesis in drug development.…”
Section: Discussionmentioning
confidence: 99%
“…For example, weak export of the antitumor polyketide doxorubicin from S. peucetius cells has been recently shown to decrease the overall productivity of the strain (Malla et al 2010, Song et al 2011). A similar situation probably applies to many recombinant pathways (Ostash et al 2010a), effectively limiting the potential of combinatorial biosynthesis in drug development.…”
Section: Discussionmentioning
confidence: 99%
“…Another representative example is the comparative proteomics on the doxorubicin less-producing mutant strain of S. peucetius ATCC 27952. 212 To increase the precursor CoA pool to support the doxorubicin production, the pantothenate kinase gene (panK) of E. coli was introduced into S. peucetius, however, doxorubicin production was instead decreased unexpectedly. Comparative proteomics revealed global proteomic changes including the decreased expression level of efflux proteins DrrAB of panK-integrated S. peucetius.…”
Section: Comparative Proteomics For Understanding and Identifying Potential Targets For Enhancing Sm Productionmentioning
confidence: 99%
“…These approaches can also be used for engineering secondary metabolite target genes to enhance antibiotic production. For example, an attempt was made to increase the coenzyme A (CoA) pool using the pantothenate kinase ( panK ) gene to enhance production of DXR in S. peucetius ATCC 27952; however, the opposite occurred due to increased aglycone polyketide ε -rhodomycinone (RHO) [89]. To understand these results in detail, 2D gel electrophoresis was used to show that the efflux protein DrrA was overexpressed, resulting in 9.4-fold higher DXR production than that of a panK integrated strain, which showed that the proteomic approach is quite useful for host development and understanding the physiology of antibiotic production.…”
Section: Engineered Proteomicsmentioning
confidence: 99%